Extraskeletal Osteosarcoma of the Thigh: An Autopsy Case Report. (5th May 2009) - Nagano, Akihito; Ohno, Takatoshi; Nishimoto, Yutaka; Yamada, Kazunari; Shimizu, Katsuji
Abstract : We report a case of extraskeletal osteosarcoma (ESOS) and autopsy findings. A 35-year-old man presented with an ossified tumor in the right thigh and lung metastasis. The lung tumors continued to develop despite multiagent chemotherapy and caused death within 8 months. Autopsy revealed many secondary lesions in the lungs, especially in the left lung. Histopathologically, the primary tumor and one of the secondary tumors showed proliferation of spindle-shaped tumor cells focally forming lace-like osteoid material. Therefore, we made a definite diagnosis of ESOS.